Shift of Power from West to East and Rise of China - Mushtaq Ahmed Abbasi; Ghulam Qumber; Ahmed Saeed Minhas (Journal of Political Studies, 2017)
This research paper is aimed at evaluating prevailing global scenario and the dynamics of shift of power from the West to the East. Efforts have been made to analyze the economic, political, and security trends to understand important aspects of the power transition process. Currently, there is an enough literature available, which proves the existing consensus among many experts that China is playing a central role in the process of shift of power from the West to the East. Therefore, while explaining this transition process, it is pertinent to focus on the leading role of China and its possible implications. So, this study further highlights the rising power of China covering an overall picture of China, particularly its economic development process, the political and cultural aspects, and the military modernization. Efforts have been made to give an analytical view that how the rise in economic power is gradually transforming itself into political, diplomatic, and military strength of China. Besides; this research effort also focuses on how China is adjusting its foreign policy posture in the regional and global affairs, which culminates or aims at adjusting itself to globalization process.